2020
DOI: 10.1093/ajcn/nqaa063
|View full text |Cite
|
Sign up to set email alerts
|

Associations between consumption of dietary fibers and the risk of cardiovascular diseases, cancers, type 2 diabetes, and mortality in the prospective NutriNet-Santé cohort

Abstract: ABSTRACT Background Mounting evidence, yet with varying levels of proof, suggests that dietary fibers (DFs) may exert a protective role against various chronic diseases, but this might depend on the DF type and source. Objectives Our objectives were to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 52 publications
2
94
0
Order By: Relevance
“…People with diabetes and those at risk for diabetes are encouraged to consume a minimum of 14 g of fiber/1,000 kcal, with at least half of grain consumption being whole, intact grains, according to the Dietary Guidelines for Americans (130). Regular intake of sufficient dietary fiber is associated with lower all-cause mortality in people with diabetes (131,132), and prospective cohort studies have found dietary fiber intake is inversely associated with risk of type 2 diabetes (133)(134)(135). The consumption of sugarsweetened beverages and processed food products with high amounts of refined grains and added sugars is strongly discouraged (130,(136)(137)(138), as these have the capacity to displace healthier, more nutrient-dense food choices.…”
Section: Carbohydratesmentioning
confidence: 99%
“…People with diabetes and those at risk for diabetes are encouraged to consume a minimum of 14 g of fiber/1,000 kcal, with at least half of grain consumption being whole, intact grains, according to the Dietary Guidelines for Americans (130). Regular intake of sufficient dietary fiber is associated with lower all-cause mortality in people with diabetes (131,132), and prospective cohort studies have found dietary fiber intake is inversely associated with risk of type 2 diabetes (133)(134)(135). The consumption of sugarsweetened beverages and processed food products with high amounts of refined grains and added sugars is strongly discouraged (130,(136)(137)(138), as these have the capacity to displace healthier, more nutrient-dense food choices.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Total dietary fibre was inversely related to circulatory disease (HRs per 10 g/day increments: 0.90; 95% CI: 0.84, 0.97 in men and 0.88; 95% CI: 0.81, 0.97 in women). In a more recent study from France dietary fibre was evaluated in 107,377 participants [33]. Both soluble fibre and insoluble fibre were inversely related with CVD risk (HR for soluble fibre 0.80; 95% CI: 0.66, 0.98, p-trend = 0.01; for insoluble fibre HR 0.65; 95% CI: 0.45, 0.94, p-trend = 0.02).…”
Section: Carbohydrates Fibre and Sugarmentioning
confidence: 99%
“…Both SFs and IFs were associated with lower risk of T2DM, while SFs were also associated with lower CVD risk. Amongst different DF sources, DFs from fruits were inversely associated with CVD risk [46]. Noteworthy, there are no RCTs on the effects of specific DF such as beta-glucan that have been shown that lowering LDL-C affects CVD outcomes.…”
Section: Effect Of Specific Df On Blood Lipids and Cvd Risk And Undermentioning
confidence: 99%